PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA PADA MATERI BANGUN DATAR KELAS IV SD NEGERI 80 PALEMBANG - Devika Amelia; Jayanti; Ida Suryani (STKIP Subang, 2023)
This study aims to produce a Canva-based interactive learning media development product on flat material, which meets the criteria of validity, practicality and effectiveness so that students are able to master the flat material easily. The type of research used is research development or Research and Development. The development model used is ADDIE The subjects of this study were fourth grade students at SD Negeri 80 Palembang. The research data were obtained from validation questionnaires, student and teacher response questionnaires and student test questions. The results of the research based on a validation questionnaire from a team of experts who have quality media display and presentation of material as a whole obtain a percentage score of 87.2% in a very valid category. Practicality questionnaire with a percentage score of 85.1% with a very practical category. The results of the effectiveness of all students obtained a percentage score of 82.3% which was obtained from students' questions about flat shapes with very effective categories. Based on the results that have been developed by the researcher entitled Development of Canva-based interactive learning media in class IV SD flat construction material, it can be concluded that the developed Canva-based interactive learning media is valid, practical and effective.